Nephrolitiasis On Nephroptosis Patient - I Made Ari Samudera; Akhada Maulana (Faculty of Medicine Universitas Mataram, 2022)
Nephroptosis or ren mobilis is defined as a descent in the anatomical position of the kidney by more than 2 corpus vertebrae (>5 cm). It is more common in women and on right kidney, although there were 10 % cases on left kidney and 20 % on bilateral kidney. Nephroptotic pain is a symptom that is often experienced by floating kidney patients. Complication of nephroptosis are hypertension and nephrolithiasis (kidney stones). Management of nephroptosis is nephropexy, or nephrectomy if there is kidney parenchymal damage. Reporting a 75-year-old female patient with right nephroptosis and kidney stone. She complained pain on the right lower abdomen that become better when patient lying. Patient has had hypertension too. On abdominal CT showed right kidney stone and severe hydronephosis. Position of the kidney was in the pelvic region. Patient then underwent right nephrectomy because parenchym of the kidney became very thin that damaged the kidney. Intra operative condition of this patient was stable, then patient discharged form hospital three days after surgery.